2008
DOI: 10.1007/s00213-008-1250-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the norepinephrine transporter improves behavioral flexibility in rats and monkeys

Abstract: Rationale Poor cognitive control, including reversal learning deficits, has been reported in children with attention deficit hyperactivity disorder, in stimulant-dependent humans, and in animal models of these disorders; these conditions have each been associated with abnormal catecholaminergic function within the prefrontal cortex. Objectives In the current studies, we sought to explore how elevations in extracellular catecholamine levels, produced by pharmacological inhibition of catecholamine reuptake prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 77 publications
7
76
0
1
Order By: Relevance
“…This finding is in general agreement with observations that executive functions are impaired by manipulations that limit noradrenergic transmission in prefrontal cortex (9,10,25) and that symptoms of various psychiatric diseases are partially alleviated with drugs that promote NE actions within the synapse (9,(26)(27)(28)(29)(30). Methylphenidate is of particular interest in this context, as Berridge and coworkers have shown previously that doses of methylphenidate, which are effective in treating symptoms of attention deficit hyperactivity disorder (ADHD) without increasing locomotion, preferentially increase NE efflux and responsiveness of individual neurons in the PFC, but not within other cortical regions (31,32).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in general agreement with observations that executive functions are impaired by manipulations that limit noradrenergic transmission in prefrontal cortex (9,10,25) and that symptoms of various psychiatric diseases are partially alleviated with drugs that promote NE actions within the synapse (9,(26)(27)(28)(29)(30). Methylphenidate is of particular interest in this context, as Berridge and coworkers have shown previously that doses of methylphenidate, which are effective in treating symptoms of attention deficit hyperactivity disorder (ADHD) without increasing locomotion, preferentially increase NE efflux and responsiveness of individual neurons in the PFC, but not within other cortical regions (31,32).…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have provided evidence of a facilitating effect of NE or LC activation on the signal-processing capabilities of various networks in the mammalian brain, but the extent to which such actions are uniform and simultaneous across forebrain terminal fields has not been resolved. Heterogeneity among LC-prefrontal projection neurons opens the door for differential actions of LC output on specified prefrontal subregions as has been suggested by selective lesion and pharmacologic studies (9,10,30,38,39). Recent work using similar experimental strategies has revealed similar novel functional and organizational principles of dopamine projections to prefrontal versus limbic terminal fields (33), thus providing considerable new insights regarding the impact of dopaminergic inputs to those circuitries in health and disease.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, several pharmacological studies have shown that drug-induced activation of the LC-NE system increases cognitive flexibility and behavioral disengagement. For example, drugs that increase tonic NE levels (i.e., mimic the effects of elevated NE release that characterize the tonic LC mode) have been found to improve attentional-set shifting and reversal learning in rats and monkeys (Seu, Lang, Rivera, & Jentsch, 2008;Lapiz, Bondi, & Morilak, 2007;Lapiz & Morilak, 2006;Steere & Arnsten, 1997;Devauges & Sara, 1990; but see Chamberlain et al, 2006). In humans, increased NE levels induced by the selective NE reuptake inhibitor atomoxetine have been found to improve the ability to stop an ongoing motor response when cued to do so (Chamberlain et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have also shown that MP and AMP, at clinically relevant doses, can significantly increase extracellular DA (Villemagne et al, 1999;Volkow et al, 1999bVolkow et al, , 2009a. Imaging studies in non-human primates have also shown significant blockade of the NE transporter at doses that are pharmacologically equivalent to those used in humans, which is interesting in light of the data indicating that enhanced extracellular catecholamine levels in cortical regions, secondary to NE reuptake inhibition, improves multiple aspects of inhibitory control over responding in rats and monkeys (Seu et al, 2009). Synaptic levels of DA and NE, under physiological conditions, act primarily as neuromodulators changing the efficacy of other transmitter signals (Keeler et al, 1989;Kiyatkin, 2002) as a function of ongoing neuronal activity (Seamans and Yang, 2004).…”
Section: Pet Imaging Studies Of Adhd Adults and Effect Of Stimulant Dmentioning
confidence: 95%